Penentuan Dimensi Terong Jepang (Soalnum melongena L) dengan Teknik Pengolahan Citra Secara Waktu Nyata - Rudiati Evi Masithoh; Yodana S. Rachmadany; Balza Achmad (agriTECH, 2006)
A real-time image processing technique was applied to determine the dimensions, i.e. length and width, of eggplants. Results showed that illuminations performed a significant role; the ideal illumination type for the experiment was TL lamp (fluorescent lamp), which was placed in perpendicular position toward conveyor. Meanwhile, the ideal eggplant-positions were longwise on the conveyor. Applying those kind of circumstances, a relationship between developed program and manual measurement of eggplant length and width showed linier equation, i.e. y = x and y = 0,99 x, respectively.